Obtaining granular activated carbon from paper mill sludge: a challenge for application in the removal of pharmaceuticals from wastewater - Jaria, Guilaine (2020)
In this work, a granular activated carbon (GAC) was produced using primary paper mill sludge (PS) as raw material and ammonium lignosulfonate (AL) as binder agent. PS is a residue from the pulp and paper industry and AL is a by-product of the cellulose pulp manufacture and the proposed production scheme contributes for their valorisation together with important savings in GAC precursors. The produced GAC (named PSA-PA) and a commercially available GAC (GACN), used as reference material, were physically and chemically characterized. Then, these materials were tested in batch experiments for the adsorption of carbamazepine (CBZ), sulfamethoxazole (SMX), and paroxetine (PAR) from ultra-pure water and wastewater. Even though GACN and PSA-PA possess very similar specific surface areas (SBET) (629 and 671 m2 g-1, respectively), PSA-PA displayed lower maximum adsorption capacities (qm) than GACN for the pharmaceuticals here studied (6 ± 1-44 ± 5 mg g-1 and 49 ± 6-106 ± 40 mg g-1, respectively). This may be related to the comparatively higher incidence of mesopores in GACN, which might have positively influenced its adsorptive performance. Moreover, the highest hydrophobic character and degree of aromaticity of GACN could also have contributed to its adsorption capacity. On the other hand, the performance of both GACs was significantly affected by the matrix in the case of CBZ and SMX, with lower qm in wastewater than in ultra-pure water. However, the adsorption of PAR was not affected by the matrix. Electrostatic interactions and pH effects might also have influenced the adsorption of the pharmaceutical compounds in wastewater.